Faktor-Faktor yang Mempengaruhi Residif Kanker Payudara - Lala Putri Andela; Asep Sukohar; Ari Wahyuni (Pusat Riset dan Inovasi Nasional, 2024)
Breast cancer is a malignant tumor that grows in the breast tissue and invades the area around the breast and can spread throughout the body. Breast cancer is the most frequently diagnosed cancer in women worldwide with 2,26 million new cases and caused 684,996 deaths worldwide in 2020. Breast cancer is ranked fifth as the loading cause of cancer death. The first rank is occupied by lung cancer. Meanwhile, in women, breasr cancer is the main cause of death due to cancer. The presence of a lumo or thickening in the breast is the most common sign and symptom, while signs and symptoms of advanced breast cancer include sunken skin, retraction or deviation of the nipple and pain, tenderness or bleeding from the nipple. Breast cancer treatment has changed over the years, both surgically and medically. Different surgical approaches to treat breast tumors include mastectomu alone or with reconstruction, either primary or delayed or Breast Conserving Therapy (BCT) aimed at reducing the risk of local postoperative recurrence. A recurrence can be characterized by weight loss, shortness, fatigue, jaundice, easy bruising or bleeding, loss of appetite, difficulty swallowing, blood in the urine or stool, and the presence of new lumps.